A note on finite group structure influenced by second and third maximal subgroups - N. P. Mukherjee; R. Khazal (International Journal of Mathematics and Mathematical Sciences, 1990)
The structure of a finite group having specified number of second and third maximal subgroups has been investigated in the paper.